Topical delivery of meropenem via spanlastic carbopol gel: in-vitro studies and in-vivo application in pressure ulcers - Abdelfattah, Shadwa; Mady, Fatma Mohamed; Sarhan, Hatem A.; Khalifa, Hazim O.; Hashem, Hamada; Hassan, Hesham; Alkhammash, Abdullah; Hadiya, Safy; Ibrahem, Reham Ali; Qelliny, Milad Reda (Frontiers in Pharmacology, 2025)
IntroductionSpanlastics, a type of elastic nanovesicle, represents a promising drug delivery system capable of encapsulating both hydrophilic and lipophilic drug compounds. These carriers are biodegradable, biocompatible, and non-immunogenic. Meropenem (MRP), a broad-spectrum carbapenem antibiotic, is widely used to treat severe infections in both adults and children before the causative pathogens are identified. However, meropenem’s aqueous formulations are highly unstable and must be administered within 24 h of preparation. This study aimed to develop a meropenem-loaded spanlastic formulation (MRP-SP) for topical application, aiming to enhance both the drug’s stability and skin permeability.MethodsSpanlastics were prepared using Span 60 and Brij 35 via the ethanol injection method. The MRP-SP formulation was extensively characterized through particle size analysis, polydispersity index (PDI), zeta potential, encapsulation efficiency, in vitro drug release, scanning electron microscopy, microbiological assays, and in vivo topical efficacy studies.Results and DiscussionThe optimized formulation (Batch F5), composed of Span 60 and Brij 35 in a 1:4 M ratio, exhibited a particle size of 462 nm, spherical morphology, 69.5% drug encapsulation efficiency, and 20% drug release within 6 h. The gel form of the same batch showed a comparable release profile. Antibacterial testing revealed that MRP-SP reduced the minimum inhibitory concentration by 2.4-fold against Pseudomonas aeruginosa compared to free MRP. Additionally, MRP-SP significantly downregulated the expression of mexA, a key resistance gene. In vivo, the topical application of MRP-SP demonstrated superior therapeutic activity in treating ulcerative skin lesions in non-diabetic mice, as evidenced by wound closure percent (89% at 10 days), wound area (49% at 10 days), and histopathological improvements. Overall, the meropenem-loaded spanlastic formulation shows strong potential as an effective topical therapy for bacterial skin infections.